PENERAPAN PEMBELAJARAN MUSIK BERBASIS GERAK UNTUK MENINGKATKAN KEMAMPUAN MOTORIK ANAK DI TK IT TAMRINUL AULAD MANYARGADING - Ruviyana Naviya Safitri; Ema Andriyani; Fu’ad Arif Noor (Rumah Riset Publisher, 2025)
This research aims to examine the effectiveness of the application of movement-based music learning in improving children's motor skills in Tamrinul Aulad IT Kindergarten. The problem faced is the lack of stimulation of children's motor development through fun and integrated learning activities. The study used a two-cycle classroom action research (PTK) method, involving 25 children aged 5-6 years. Data was collected through observation, interviews, and documentation, then analyzed in a qualitative descriptive manner. Movement-based music learning is applied through various activities such as movement and song, rhythmic music playing, and creative dance. The results showed a significant improvement in children's gross and fine motor skills. In cycle I, 60% of children achieved the expected development criteria (BSH), increasing to 85% in cycle II. Aspects that have improved include coordination of movement, balance, muscle strength, and the ability to follow rhythm. Movement-based music learning also has a positive impact on the social-emotional aspects of children, increases enthusiasm for learning, and creates a fun learning atmosphere. The study concluded that movement-based music learning is effective in improving early childhood motor skills and can be recommended as a learning strategy in early childhood educational institutions.